Non-Stoichiometric BaxMn0.7Cu0.3O3 Perovskites as Catalysts for CO Oxidation: Optimizing the Ba Content - Álvaro Díaz-Verde; Emerson Luiz dos Santos Veiga; Héctor Beltrán-Mir; María José Illán-Gómez; Eloísa Cordoncillo-Cordoncillo (Nanomaterials)
In this work, a series of BaxMn0.7Cu0.3O3 samples (x: 1, 0.9, 0.8, and 0.7, BxMC) was synthesized, characterized, and used as catalysts for CO oxidation reaction. All formulations were active for CO oxidation in the tested conditions. A correlation between the electrical conductivity, obtained by impedance spectroscopy, and the reducibility of the samples, obtained by H2-TPR, was observed. The Ba0.8Mn0.7Cu0.3O3 composition (B0.8MC) showed the best catalytic performance (comparable to that of the 1% Pt/Al2O3 reference sample) during tests conducted under conditions similar to those found in the exhaust gases of current gasoline engines. The characterization data suggest the simultaneous presence of a high Mn(IV)/Mn(III) surface ratio, oxygen vacancies, and reduced copper species, these two latter being key properties for ensuring a high CO conversion percentage as both are active sites for CO oxidation. The reaction temperature and the reactant atmosphere composition seem to be the most important factors for achieving a good catalytic performance, as they strongly determine the location and stability of the reduced copper species.